Decreased Deposition of Beta-Amyloid 1-38 and Increased Deposition of Beta-Amyloid 1-42 in Brain Tissue of Presenilin-1 E280A Familial Alzheimer’s Disease Patients - Dinkel, Felix; Trujillo-Rodriguez, Diana; Villegas, Andres; Streffer, Johannes; Mercken, Marc; Lopera, Francisco; Glatzel, Markus; Sepulveda-Falla, Diego (Frontiers in Aging Neuroscience, 2020)
Familial Alzheimer’s Disease (FAD) caused by Presenilin-1 (PS1) mutations is characterized by early onset, cognitive impairment and dementia. Impaired gamma secretase function favors production of longer beta-amyloid species in PS1 FAD. The PS1 E280A mutation is the largest FAD kindred under study. Here, we studied beta-amyloid deposits in PS1 E280A FAD brains in comparison to sporadic Alzheimer’s disease (SAD). We analyzed cortices and cerebellum from 10 FAD and 10 SAD brains using immunohistochemistry to determine total beta-amyloid, hyperphosphorylated tau (pTau) and specific beta-amyloid peptides 1-38, 1-40, 1-42 and 1-43. Additionally, we studied beta-amyloid subspecies by ELISA, and vessel pathology detected with beta-amyloid 1-42 and truncated pyroglutamylated beta-amyloid antibodies. There were no significant differences in total beta-amyloid signal between SAD and FAD. Beta-amyloid 1-38 and 1-43 loads were increased and 1-42 loads were decreased in frontal cortices of SAD when compared to FAD. Beta-amyloid species assessment by ELISA resembled our findings by immunohistochemical analysis. Differences in beta-amyloid 1-38 and 1-42 levels between SAD and FAD were evidenced by using beta-amyloid length-specific antibodies, reflecting a gamma secretase-dependent shift in beta-amyloid processing in FAD cases. The use of beta-amyloid length-specific antibodies for post-mortem assessment of beta-amyloid pathology can differentiate between SAD and PS1 FAD cases and it can be useful for identification of SAD cases potentially affected with gamma secretase dysfunction.